2021
DOI: 10.1002/cnr2.1514
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing cervical cancer screening practice among female health workers in Nigeria: A systematic review

Abstract: Background: Cervical cancer is the most prevalent gynaecologic cancer in Nigeria.Despite being largely preventable through screening, cervical cancer is the second leading cause of cancer morbidity and mortality in Nigeria. To reduce the burden of cervical cancer in Nigeria, female health workers (FHWs) are expected to play an influential role in leading screening uptake and promoting access to cervical cancer education and screening. Aim: The aim of this systematic review is to assess the factors influencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 58 publications
2
25
0
3
Order By: Relevance
“…The findings of the study revealed that the level of utilization of cervical cancer screening services was moderate Ifemelumma, et al (2019) however noted that the uptake of cancer of the cervix screening services was poor with only 20.6% having been screened. Okolie, et al (2021) revealed that CCS uptake was poor with common barriers being the cost of screening, fear of positive results, lack of test awareness, reluctance to screen, low-risk perception, and lack of time.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…The findings of the study revealed that the level of utilization of cervical cancer screening services was moderate Ifemelumma, et al (2019) however noted that the uptake of cancer of the cervix screening services was poor with only 20.6% having been screened. Okolie, et al (2021) revealed that CCS uptake was poor with common barriers being the cost of screening, fear of positive results, lack of test awareness, reluctance to screen, low-risk perception, and lack of time.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Nigeria’s weak health system and lack of a cervical cancer control policy that facilitates a roadmap for the country’s fight against cervical cancer are considered principal problems [ 13 , 14 ]. Similarly, factors such as poor awareness, low-risk perception, poverty, lack of female providers, fear of positive screening result and sociocultural norms contribute immensely to poor uptake of CCS services among Nigerian women [ 15 , 20 ].…”
Section: Cervical Cancer Screening Outcomes In Nigeriamentioning
confidence: 99%
“…The role of health workers, especially female nurses, in tackling Nigeria’s rising cervical cancer burden has been a vital part of ongoing calls to maximise opportunistic screening activities [ 15 , 16 ]. Traditionally, female nurses, including midwives, play a critical role in the delivery of reproductive health services, including CCS services, to eligible women [ 26 – 28 ].…”
Section: Spotlight On Female Nurses’ Role In Cervical Cancer Screenin...mentioning
confidence: 99%
See 2 more Smart Citations